AMNESTY INTERNATIONAL’S ROLE IN HANDLING HUMAN RIGHTS VIOLATIONS CASES IN THE THAI MILITARY JUNTA REGIME 2014-2023 - Syahab, Sayid Muhammad Zidan (Journal of Innovation Research and Knowledge, 2025)
The 2014 military coup in Thailand, led by General Prayuth Chan-ocha, established the National Council for Peace and Order (NCPO), which ruled the country with authoritarian control for nearly a decade. This era was marked by serious human rights violations, including torture, enforced disappearances, suppression of free expression, and the rejection of asylum for Rohingya refugees—violations of Articles 3, 5, 9, 14, and 19 of the Universal Declaration of Human Rights (UDHR). This study explores the role of Amnesty International in addressing these abuses through Clive Archer's theory, which views international organizations as instruments, arenas, and actors. Utilizing a qualitative descriptive method and literature review, the research finds that Amnesty International actively documented violations, initiated global campaigns, and facilitated international advocacy. While the organization contributed significantly to raising international awareness and mobilizing diplomatic pressure, its influence on Thai domestic policy remains limited due to entrenched political resistance. Nonetheless, Amnesty's actions were crucial in preserving discourse on human rights and empowering civil society. It serves as a vital transnational actor whose role, although constrained, remains symbolically and normatively important in the struggle for human rights in authoritarian contexts.